Differences in Hormonal Signaling Triggered by Two Root-Feeding Nematode Species Result in Contrasting Effects on Aphid Population Growth - van Dam, Nicole M.; Wondafrash, Mesfin; Mathur, Vartika; Tytgat, Tom O. G. (Frontiers in Ecology and Evolution, 2018)
Belowground feeding herbivores can affect their aboveground counterparts via systemic induced responses. Hormonal signaling pathways, such as the jasmonic acid (JA) and salicylic acid (SA) pathways, play a pivotal role in shaping such aboveground-belowground herbivore interactions. In this study, we analyzed the effects of two root-feeding nematode species, the cyst nematode Heterodera schachtii, and the root knot nematode Meloidogyne hapla, on the preference and performance of cabbage aphids Brevicoryne brassicae. The two sedentary nematodes differ in their feeding strategies and in which plant responses they trigger. We tested the hypothesis that differences in aphid preference and performance are governed by differences in systemic defense signaling triggered by the nematodes. When allowed to choose, aphids showed a lower preference for black mustard (Brassica nigra) plants infested with H. schachtii compared to uninfested plants. On these plants their population increase was reduced as well. Gene expression analyses revealed that aphid infestation on H. schachtii-infested plants strongly induced PR1, a marker gene for the SA-–pathway. The expression of the JA marker genes VSP2 and MYC2 was repressed. On the other hand, M. hapla infestation increased aphid preference and population growth compared to those on control plants. Aphid feeding upregulated the expression of VSP2 and MYC2, whereas PR1 expression was not induced. Interestingly, aphid infestation on plants without nematodes did not activate any of the signaling pathways. This suggests that H. schachtii infestation systemically enhanced aphid induced-resistance via the SA pathway. In contrast, M. hapla infestation enhanced JA-pathway regulated responses. This may reduce SA-induced resistance to aphid infestation via negative JA-SA cross-talk. Based on our results, we conclude that the differences in the interactions of aphids with cyst and root knot nematodes emerge from differences in the plant responses triggered by both nematodes. Our results show that aboveground herbivore performance on plants infested with different nematode species may be strongly associated with nematode feeding strategies.